2020
DOI: 10.1001/jamanetworkopen.2020.9637
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Visit Characteristics Associated With Use of Direct Scheduling in Primary Care Practices

Abstract: Key Points Question What characteristics are associated with the online portal–based scheduling of medical visits? Findings In this cross-sectional study of 62 080 patients and 134 225 completed visits at 17 primary care practices within a large academic medical center, early adopters of direct scheduling were more often young, White, and commercially insured. Compared with visits scheduled by speaking with clinic staff in person or by telephone, directly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 22 publications
(60 reference statements)
4
38
0
Order By: Relevance
“…1,24,25 The primary reason could be that younger patients tend to miss appointments because of school, work, and family responsibilities. A secondary reason could be that younger people are more likely than older patients to make appointments online, which is consistent with Ganguli et al 26 In most previous studies, 1,21,27,28 scheduling-appointment interval was a strong predictor of no-shows; the greater the amount of time, the greater the risk of noshow. Cronin et al, for example, found that missed appointment rates increased with a longer wait between scheduling and appointment because of an increased likelihood of forgetting, among other reasons.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…1,24,25 The primary reason could be that younger patients tend to miss appointments because of school, work, and family responsibilities. A secondary reason could be that younger people are more likely than older patients to make appointments online, which is consistent with Ganguli et al 26 In most previous studies, 1,21,27,28 scheduling-appointment interval was a strong predictor of no-shows; the greater the amount of time, the greater the risk of noshow. Cronin et al, for example, found that missed appointment rates increased with a longer wait between scheduling and appointment because of an increased likelihood of forgetting, among other reasons.…”
Section: Discussionsupporting
confidence: 81%
“… 1 , 24 , 25 The primary reason could be that younger patients tend to miss appointments because of school, work, and family responsibilities. A secondary reason could be that younger people are more likely than older patients to make appointments online, which is consistent with Ganguli et al 26 …”
Section: Discussionsupporting
confidence: 80%
“…One study found that patient portal use was lower among Black (vs White) patients; Medicare, Medicaid, and uninsured (vs commercially insured) patients; and patients with decreased neighborhood broadband internet access [14]. Other studies using data prior to the COVID-19 pandemic have additionally suggested that telemedicine and patient-facing health information technology utilization is lower among men, patients over 65 years, non-White patients, patients without commercial insurance, and patients living in neighborhoods with low internet access; this lack of internet access and technology proficiency continues to impede wider adoption of health information technology among racial minorities and those without commercial insurance [15][16][17][18]. Given prior research on the benefits of telemedicine interventions on clinical outcomes, such as improvement in glycemic control in medically underserved patients with diabetes, these disparities in the use of and access to digital health may directly translate into disparities in health care quality [19].…”
Section: Introductionmentioning
confidence: 99%
“…The countries covered in the review include the United States [ 18 , 28 , 29 , 31 , 33 , 35 , 37 , 43 , 73 , 74 ], Taiwan [ 22 , 23 , 42 ], England [ 19 , 34 , 69 , 72 ], China [ 24 , 48 , 75 ], Australia [ 45 , 70 , 71 ], Canada [ 36 ], Iran [ 5 , 32 , 47 ], and the Philippines [ 26 ]. Another article included 7 countries in Europe [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first article retrieved for the scoping study was published in 2004 [ 18 ], with ≤3 articles each year up to and including 2019. In 2020, 8 articles [ 22 , 26 , 28 , 29 , 31 , 37 , 72 , 73 ] featuring barriers to and facilitators of automated self-scheduling were published. Table 2 displays the number of articles published by year of publication.…”
Section: Resultsmentioning
confidence: 99%